PENGEMBANGAN MODUL AJAR KURIKULUM MERDEKA MATA PELAJARAN BAHASA INGGRIS SMK KOTA SURABAYA - Rahmat Setiawan; Nukmatus Syahria; Ferra Dian Andanty; Salim Nabhan (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2022)
The following workshop is done with the aim to socialize the ways to develop teaching module for Independent Curriculum especially for English subject, since there are still many English teachers who are confused in arranging the teaching module. The data is taken from questionnaire. The participants in this study is the English eachers from Vocational High School in Surabaya. There are 5 questions in the questionnaire. The results showed that the English teachers from Vocational High School in Surabaya is enthusiastic to join the workshop and to create the teaching module after the workshop finished. Previously, many of them were still confused about preparing learning modules due to various perceptions, after attending the workshop they had the same perceptions in developing teaching module and they were more confident in creating it.